2021
DOI: 10.1038/s41598-021-88095-w
|View full text |Cite
|
Sign up to set email alerts
|

Automatic 3D dense phenotyping provides reliable and accurate shape quantification of the human mandible

Abstract: Automatic craniomaxillofacial (CMF) three dimensional (3D) dense phenotyping promises quantification of the complete CMF shape compared to the limiting use of sparse landmarks in classical phenotyping. This study assesses the accuracy and reliability of this new approach on the human mandible. Classic and automatic phenotyping techniques were applied on 30 unaltered and 20 operated human mandibles. Seven observers indicated 26 anatomical landmarks on each mandible three times. All mandibles were subjected to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Only one of the observers was trained in cranial landmarking, resulting in a significantly lower overall RMS error (0.66mm) in comparison to the other two observers (1.11mm and 0.94mm). These values are similar to those reported in other studies [27, 30, 31], albeit slightly higher than findings from a study employing specialized landmarking software at some landmarks [31]. As expected, the inter-observer error was higher (1.44mm).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Only one of the observers was trained in cranial landmarking, resulting in a significantly lower overall RMS error (0.66mm) in comparison to the other two observers (1.11mm and 0.94mm). These values are similar to those reported in other studies [27, 30, 31], albeit slightly higher than findings from a study employing specialized landmarking software at some landmarks [31]. As expected, the inter-observer error was higher (1.44mm).…”
Section: Discussionsupporting
confidence: 91%
“…Analysis revealed a variation in Euclidean distance between manual and automatic landmarks ranging from 0.10mm - 7.24mm, with an average of 1.5mm. Notably, landmarks exhibiting higher values were often associated with regions that were less effectively masked (e.g., gonion where the mask did not always align with the edge of the skull) and were prone to higher inter-observer errors, as observed in previous studies [30]. Previous research has reported comparable errors between manual and automatic landmark placements ranging from 2.19mm [31], 1.4mm [30], 2.01mm [42] and 1.26mm [27].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The first approach performs a rigid alignment of the template mesh to match the target, followed by deformable registration to refine the match, then transfers the landmarks from the atlas to the target mesh. Examples are ALPACA [5, 6] and MeshMonk [7, 8], which mainly differ in their non-rigid registration algorithm. Variants of this approach abolish landmarks altogether and achieve correspondences between the vertices of the meshes directly [3, 9].…”
Section: Introductionmentioning
confidence: 99%